300 GHz vector‐sum phase shifter using InP DHBT amplifiers. Issue 4 (1st February 2013) - Yu, H.G.; Lee, K.J.; Kim, M.
Abstract : A vector‐sum phase shifter that provides 90° phase control with a positive signal gain is successfully demonstrated at WR‐3 band. The integrated circuit consists of input and output microstrip power dividers and two InP DHBT amplifiers with a 300 GHz gain of 14.8 dB. The measurements on a fabricated phase shifter show offset phases of − 46°, − 22°, 0°, 25°, 57° and signal gain of 7.7 to 10.1 dB at 300 GHz.